Analysis of maturity information technologies exams - Blonskis, Jonas; Dagienė, Valentina; Burbaitė, Renata (Lietuvos matematikos rinkinys, 2008)
The paper deals with the tasks of maturity information technologies exams of 2006, 2007 and the pilot exam of 2007 adequacy to calibre standards, question resolution and its toughness. It was identified, that the attitude to exam matrix of pupils, who were preparing themselves for the maturity exam, and attitude of experts, who were preparing tasks for mentioned exam, is unequal: experts and pupils differently perceive and treat knowledge and solution of problems. There were abstracted special question groups, which differentiate knowledge and abilities of pupil. It was also signified, which mistakes are more common for pupils, what are the reasons of them, giving recommendations for teachers.